IDA PEDANDA KANIA:REPRESENTASI PERAN PEREMPUAN DALAM UPACARA AGAMA HINDU DI KARANGASEM - Mandala Keniten, Ida Ayu Putu Citta; Punia, I Nengah; Sastri Mahadewi, Ni Made Anggita (JURNAL ILMIAH SOSIOLOGI (SOROT), 2020)
This study aims to describe and analyze more deeply about the highest participation and role of women in Hindu religious ceremonies. This research uses a qualitative approach with descriptive and exploratory types. The theory used in this study is the theory of performance from Judith Butler. The theory analyzes the identity of individuals will be formed on the performance that they do repeatedly and consistently. The results showed that the role played by Ida Pedanda Kania is one form of implementation of gender mentioned according to Judith Butller, ie someone having a gender that is different from gender is the result of the role they play so as to give birth to a new identity. This shows that becoming a leader of Hindu religious ceremonies in Bali is not limited to mere kelanin types. Men or women have the same rights to be ceremonial leaders. Keywords: the role of women, religious ceremonies, ceremonial leaders, performance, identity